PENGARUH KREDIBILITAS BTS PADA IKLAN TELEVISI TOKOPEDIA TERHADAP PEMBENTUKAN CITRA MEREK : (Survei Kepada Pengguna Tokopedia) - Amelia Tri Puspita Ningrum (2020)
E-commerce industry competition in Indonesia is getting tougher so that e-commerce business people in Indonesia must be able to plan the right marketing communication strategy, one of which is through advertising. Advertising is the process of delivering persuasive messages from the company to the consumer claon. In an advertisement, the role of an ad star is very important because it is both a spokeperson and the identity of the advertised brand. So, research and consideration are needed to determine the eligibility of an advertising star. This study discusses the role of advertising star credibility in forming Tokopedia brand image. Which is the role of an ad star always related to the identity and image of a brand. This study aims to determine how much influence the BTS as an advertisement star has had on the formation of the Tokopedia brand image and to determine the comparison of its influence between Tokopedia users who are K-pop fans or Tokopedia users who are not K-pop fans. This study uses a quantitative method with an explanatory type and uses a questionnaire as a survey method. The population and sample in this study were Tokopedia e-commerce users. With a total sample of 100 respondents and the sampling technique used is probability sampling with the type of random sampling. The theory used in this research is source credibility theory. Tokopedia brand image is measured by the credibility of the ad star, namely BTS which consists of three elements, namely expertise, trust and attractiveness. The results of the correlation test are the X variable (BTS credibility) to the Y variable (Brand Image) showing a strong correlation with a value of 0.784. The results of the determination coefficient test are known to be 54.3%. Then the results of hypothesis testing with t arithmetic 9.911 it can be concluded that Ha is accepted and Ho is rejected. This means that there is an influence of BTS Credibility on Tokopedia Television Ads on the Formation of Brand Image in Tokopedia users. The suggestion of this research is that the decision in choosing an ad star requires in depth research and consideration and is supported by the right strategy to fit the target audience segmentation and goals to be achieved. It aims to assess the suitability of the ad star with the campaign that is being or will be run.